RELIABILITY AND ACCURACY OF TOMOGRAPHIC 3D ULTRASOUND FOR GRADING VESSEL STENOSIS: A PHANTOM STUDY - Al Zahrani, Adel; Aslam, Mohammed; Sultan, Salahaden R (Ultrasound in medicine & biology, 2024)
IntroductionCVD is a term used for a number of pathologies affecting the heart and blood vessels, including coronary heart disease, cerebrovascular disease, and peripheral arterial disease (102). CVD is of- ever increasing health concern affecting all ages, genders, races, and ethnicities and is associated with 17.8 million deaths annually worldwide (103). Atherosclerotic plaques in arteries are a major cause of CVD (104). The build-up of large atherosclerosis can lead to severe stenosis or occlusion of arteries influencing blood perfusion to distal tissues (105). The degree of luminal stenosis and features of atherosclerotic plaques are essential when choosing an optimal intervention (106,107). thus, accurate assessment grading of stenosis caused by atherosclerosis is necessary. Blood vessels and atherosclerosis plaques are 3D structures in nature that can be accurately assessed with 3D imaging (108,109). An attempt to quantify vessel size and volume, luminal stenosis, and plaque morphological features using a 2D imaging method may provide inaccurate outcomes. 2DUS is the current first-line imaging method for demonstrating arterial wall thickness, plaque surface regularity and morphology, and grading of stenosis through diameter reduction (DR) and area reduction (AR). However, ulcerated plaque may be misdiagnosed with irregular plaque surface in addition to the difficulty of detecting echolucent plaque (109). Furthermore, imaging vessel stenosis using a 2D scanning technique can be mis-graded and may result in over or under-estimation of stenosis (44,100,110–113). Several studies that compared the use of 3DUS to 2DUS showed that 3DUS is superior for the quantification of vascular disease and can provide more information on plaque morphology and degree of stenosis (114–119). Other studies assessing the use of 3DUS for the evaluation of vascular diseases and changes in plaque volume in response to treatments reported that 3DUS imaging has the ability to determine total plaque volume accurately and risk stratification, vessel wall volume, ulceration, echolucency and plaque texture (86,109,120), suggesting that 3DUS can be used as a rapid diagnostic tool for vascular diseases and for treatment evaluation of surgical and medical interventions. MethodA high-resolution premium Philips Elite ultrasound imaging system (Philips Healthcare, Bothell, WA, USA) was used to obtain the maximum percentage of stenosis from a peripheral vascular phantom using 2DUS and t3DUS (PIUR imaging GmbH, Vienna, Austria) imaging techniques. Inter- operator reproducibility and accuracy of DR and AR 2DUS and t3DUS in measuring maximum stenosis percentage were assessed. Two experienced certified clinical sonographers with efficient training on t3DUS (operator A and operator B) were asked to measure the maximum percentage of stenosis from all channels with stenosis. Both operators were blinded to each other`s measurements and the reference of the manufacturer's maximum percentage of stenosis of all channels. Ethical approval was not required as animals, or human subjects were not involved in this study. The maximum percentage of stenosis was measured on a peripheral vascular phantom model 525, produced by Computerized Imaging Reference Systems, Inc. (CIRS, Norfolk, Virginia, USA). The phantom is made from urethane rubber tissue-mimicking materials, including four channels (channel 1 with no stenosis, channel 2 with 50% stenosis, channel 3 with 75% stenosis, and channel 4 with 90% stenosis) at a depth of approximate 1.5 cm from the scan surface, simulating superficial vasculature. The acoustic properties of tissue-mimicking materials can be affected by temperature variations. According to the phantom operating manual, the tissue-mimicking material has a sound velocity of 1450 m/s at 0.5 dB/cm/MHz at room temperature (≈23°C). Our measurements were taken at a temperature of 22-24°C based on the thermometer affixed to the phantom and a hand-held thermometer to ensure measurement accuracy (Figure 4.1). ResultsA total of 540 measurements of maximum stenosis percentage were obtained using DR and AR 2DUS and t3DUS imaging techniques. On a visit, each operator acquired 270 stenosis percentage measurements from three channels simulating superficial vasculature (90 and 30 measures per technique and channel, respectively). Measurements of the maximum percentage of channels with 50% stenosis (A-C), 75% stenosis (D-F) and 90% stenosis (G-I) using DR 2DUS, AR 2DUS and t3DUS in peripheral vascular phantom (Model 525, Computerized Imaging Reference Systems). AR: area reduction, DR: Diameter reduction, 2DUS: 2D ultrasound, t3D: tomographic 3D ultrasound. ConclusionFree-hand t3DUS is a reproducible and accurate imaging method for grading stenosis. Interoperator reproducibility of t3DUS for grading stenosis was excellent, with a low coefficient of variation. The mean difference of stenosis measurements from manufacturer reference values for all channels was low in t3DUS than in 2DUS. There was a significant under and over-estimation of 2D DR and AR, respectively, compared to t3DUS. Other phantom and human studies investigating the reliability of t3DUS for grading stenosis and additional metrics, including plaque volume, are required. In the next chapter, the use of 3D ultrasound for the measurement of carotid plaque volume is presented.